Smart Home Users’ Information in Cloud System: A Comparison Between Malaysian Personal Data Protection Act 2010 And EU General Data Protection Regulation - Basarudin, Noor Ashikin; Yeon, Asmah Laili; Mohamed Yusoff, Zuryati; Md Dahlan, Nuarrual Hilal; Mahdzir, Nazli (Construction Research Institute of Malaysia (CREAM), 2017)
Security of data in cloud systems plays a significant role in ensuring trust from the users. It is also a method of warranting a well-working system in house smart concept by offering a number of services to the homeowner, especially in data management and data storage. However, the immense benefits offered by the cloud system are associated with a number of uncertainties which have created the issue of confidentiality and data safety. This article adopts a doctrinal legal study that analyses the Personal Data Protection Act 2010 on the aspect of protection conferred to cloud users and with reference to an additional point that is well addressed in the European Union General Data Protection Regulation. The overall finding shows that there are still loopholes in the Act which need to be investigated to improve and cater to the needs of legal policy in protecting the personal data of smart home users in the cloud.